Petrographic and Geochemical Characteristics of the Djabatoure Massif Metamagmatites from the Pan-African Orogen in Central Togo, West Africa - Malibida Kpanzou, Sarakawa Abalo; Alayi, Gnanwasou; Agbossoumondé, Yao; Tairou, Mahaman Sani; González-Jiménez, José María; Garcia-Casco, Antonio (European Scientific Journal, ESJ, 2023)
The Dahomeyide orogen, in Togo and adjoining parts of southeast Ghana and Benin, represents the suture of West Africa Craton (WAC) into northwest Gondwana. The suture zone corresponds to a narrow and lithologically diverse area with high pressure granulite complexes. The Djabatoure massif, located in the central part of Togo, belongs to the suture zone. The aim of this paper is to present the petrographic and geochemical characteristics of the Djabatoure massif in order to better understand the geodynamic evolution of the Dahomeyide belt in Togo. The methodology implemented is based on a synthesis of previous works, a petrographic study of 20 thin sections, and a geochemical study through discrimination diagrams of 15 rock samples. Results show that the Djabatoure massif is composed of granulites, pyroxenites, amphibolites, talcschists and gneisses. These rocks were equilibrated under granulite facies conditions and subsequently partially retrogressed to the amphibolite facies. The Djabatoure massif rocks also display tholeiitic affinity, enriched LREE, and negative anomalies in Nb, Zr and Ti; all these characteristics indicate subduction zone magmtism. These features are consistent with protoliths of tholeiites, N-MORB, and volcanic arc basalts affinities. The Djabatoure massif rocks were emplaced in an oceanic environment and likely originated from a metasomatized mantle.